Acute Heart Failure in Multisystem Inflammatory Syndrome in Children in the Context of Global SARS-CoV-2 Pandemic. Issue 5 (4th August 2020) - Belhadjer, Zahra; Méot, Mathilde; Bajolle, Fanny; Khraiche, Diala; Legendre, Antoine; Abakka, Samya; Auriau, Johanne; Grimaud, Marion; Oualha, Mehdi; Beghetti, Maurice; Wacker, Julie; Ovaert, Caroline; et al.
Abstract : Background: Cardiac injury and myocarditis have been described in adults with coronavirus disease 2019 (COVID-19). Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in children is typically minimally symptomatic. We report a series of febrile pediatric patients with acute heart failure potentially associated with SARS-CoV-2 infection and the multisystem inflammatory syndrome in children as defined by the US Centers for Disease Control and Prevention. Methods: Over a 2-month period, contemporary with the SARS-CoV-2 pandemic in France and Switzerland, we retrospectively collected clinical, biological, therapeutic, and early outcomes data in children who were admitted to pediatric intensive care units in 14 centers for cardiogenic shock, left ventricular dysfunction, and severe inflammatory state. Results: Thirty-five children were identified and included in the study. Median age at admission was 10 years (range, 2–16 years). Comorbidities were present in 28%, including asthma and overweight. Gastrointestinal symptoms were prominent. Left ventricular ejection fraction was <30% in one-third; 80% required inotropic support with 28% treated with extracorporeal membrane oxygenation. Inflammation markers were suggestive of cytokine storm (interleukin-6 median, 135 pg/mL) and macrophage activation (D-dimer median, 5284 ng/mL). Mean BNP (B-type natriuretic peptide) was elevated (5743 pg/mL). Thirty-one of 35 patients (88%) tested positive for SARS-CoV-2 infection by polymerase chain reaction of nasopharyngeal swab or serology. All patients received intravenous immunoglobulin, with adjunctive steroid therapy used in one-third. Left ventricular function was restored in the 25 of 35 of those discharged from the intensive care unit. No patient died, and all patients treated with extracorporeal membrane oxygenation were successfully weaned. Conclusions: Children may experience an acute cardiac decompensation caused by severe inflammatory state after SARS-CoV-2 infection (multisystem inflammatory syndrome in children). Treatment with immunoglobulin appears to be associated with recovery of left ventricular systolic function. Abstract : Supplemental Digital Content is available in the text.